PRE-ALEXANDROFF SPACE - Ayed .E. Hashoosh Al-Badry (University of Thi-Qar Journal of Science, 2019)
In this paper we introduce a new definition of the topological space weaker of Alexandroff space, namelypre-Alexandroff space. These spaces are which arbitrary intersection of an open set is a pre-open set. Inaddition to give a new definition of minimal pre-open sets and investigate about some of its properties, alsowe get some theorems and result related to this space.